Pemahaman Akuntansi dan Kemampuan Pelaku UMKM Terhadap Penyajian Laporan Keuangan - Novatiani, R. Ait; Christina, Veronica; Bachtiar, Bachtiar; Novianto, Robertus Ary; Sarumpet, Tetty Lasniroha; Wijaya, Aida (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
Many MSME actors in carrying out their business activities do not carry out accounting books, especially in their operational activities, which have an impact on not presenting financial reports, this is due to inadequate understanding of accounting and MSME actors do not have the ability to present quality financial reports. The purpose of the research is to partially analyse the understanding of accounting and the ability of MSME actors to present financial statements. The sample is 65 MSME players in the industrial sector in Mekarmanik Village, Cimenyan District, Bandung Regency. The findings prove that partially accounting understanding and the ability of MSME actors affect the presentation of financial statements.